NARRATIVE RESEARCH IN URBAN RESEARCH: THE ANALYSIS OF EVERYDAY PRACTICES FOR THE UNDERSTANDING OF FRAGMENTARY SOCIO-SPATIAL LOGIC - Batista, Selma Paula Maciel (2023)
In this article, we use everyday life as a guiding thread to explore the spatial practices of mobility, consumption, leisure and work in the urban space. To do this, we use the narratives of three women living in medium and high-end closed residential areas in the city of Presidente Prudente, in the west of the state of São Paulo, Brazil. The semi-structured interview procedure was used for this recording and, for analysis and interpretation, we employed the systematization strategies typical of narrative research. In addition, based on the location of the residences, the georeferencing of the routes of spatial practices and the radius of mobility to identify areas of common convergence between the interviewees, it was possible to observe the superimposition of fragmented socio-spatial logic on the central-peripheral urban structure.